PENGARUH PERTUMBUHAN PENJUALAN DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - MJ, Ermad; Umar, Zulkifli (JURNAL KEBANGSAAN, 2018)
This study aims to determine the effect of sales growth and profitability on capital structure, both simultaneous and individually. This study is a census research, which includes all basic industrial and chemical companies listed on the Indonesia Stock Exchange that have met the criteria in the observation data. The observation period of 2015-2017 research data totaling 30 companies. The analytical method used is multiple linear regression. The results of this study found sales growth and profitability affect the capital structure, both simultaneous and individually. Keywords: Capital structure, sales growth, profitability